Pemetaan Kompetensi Perangkat Desa Melalui Asesmen Psikologis dan Teknis dalam Mendukung Penataan Jabatan Berbasis Merit Sistem - Wawan Shokib Rondli; Edris Zamroni; Umi Khoiriyah; Josep Wibi Khris Setya; Trendy Wijayanti; Yudha Prasetyo (Universitas Muria Kudus, 2026)
Improving the quality of village officials is an important factor in supporting effective governance and optimal public service delivery. This community service activity aimed to map the competencies of village officials in Kedungdowo Village through psychological assessments and the measurement of technical job knowledge. The methods employed included the Edwards Personal Preference Schedule (EPPS) personality test, the Lee-Thorpe Occupational Interest Test, and a technical knowledge test related to village governance based on the regulatory framework for village officials in Kudus Regency. A total of 11 village officials participated in the assessment, and the results were analyzed using a triangulation approach that integrated personality traits, job interests, and technical competencies. The findings indicate that each individual demonstrates a distinct competency profile, highlighting the importance of aligning job placement with psychological characteristics and technical abilities. The recommendations generated from this activity can serve as an objective basis for village governments to implement merit-based personnel management, thereby enhancing the effectiveness and quality of public service delivery at the village level.